Journalistic Responses to Technological Innovation in Newsrooms: An exploratory study of Twitter use. Issue 8 (16th November 2016) - Chadha, Kalyani; Wells, Rob
Abstract : This study seeks to investigate how journalists at leading national US newspapers and wire services grapple with the impact of technological changes, especially the introduction and growing use of social media in newsrooms. Using a qualitative methodological approach involving in-depth, semi-structured interviews with journalists employed at leading national and regional news organizations such as The New York Times, The Washington Post, The Wall Street Journal, Los Angeles Times, The Dallas Morning News, Bloomberg News, Reuters and the Associated Press, we explore how journalists view the impact of the growing use of social media, specifically Twitter, on their work environment. We find that while they acknowledged that Twitter facilitated aspects of their work, they almost universally perceived the growing use of this technology as contributing to a variety of tensions and potential conflicts within the newsroom.